Interface-engineered non-volatile visible-blind photodetector for in-sensor computing - Ge Li; Donggang Xie; Qinghua Zhang; Mingzhen Zhang; Zhuohui Liu; Zheng Wang; Jiahui Xie; Erjia Guo; Meng He; Can Wang; Lin Gu; Guozhen Yang; et al. (Nature Communications)
Abstract Ultraviolet (UV) detection is extensively used in a variety of applications. However, the storage and processing of information after detection require multiple components, resulting in increased energy consumption and data transmission latency. In this paper, a reconfigurable UV photodetector based on CeO2/SrTiO3 heterostructures is demonstrated with in-sensor computing capabilities achieved through interface engineering. We show that the non-volatile storage capability of the device could be significantly improved by the introduction of an oxygen reservoir. A photodetector array operated as a single-layer neural network was constructed, in which edge detection and pattern recognition were realized without the need for external memory and computing units. The location and classification of corona discharges in real-world environments were also simulated and achieved an accuracy of 100%. The approach proposed here offers promising avenues and material options for creating non-volatile smart photodetectors.